The Role of Leader Support in Facilitating Proactive Work Behavior: A Perspective From Attachment Theory - Wu, C.; Parker, Sharon (Sage Publications, Inc., 2017)
Researchers have proposed that leader support helps employees behave proactively at work. Leader support can facilitate the opportunities for employees to bring about change, as well as their motivation to do so. Nevertheless, empirical studies have shown mixed effects of leader support on employees’ proactive behavior. In this study, to reconcile the inconsistent findings on the impact of leader support on employees’ proactive behavior, the authors consider the content, mediating mechanisms, and boundary conditions of leader support in shaping employees’ proactive behavior. On the basis of attachment theory, the authors propose that secure-base support from leaders (support in the form of leader availability, encouragement, and noninterference) positively predicts employees’ proactive work behavior by increasing their role breadth self-efficacy and autonomous motivation. These hypotheses are supported in an online-survey sample from U.S. participants (N = 138) and a sample from a large gas and oil company in China (N = 212). The authors further propose that the beneficial effects of secure-base support from leaders are more prominent for individuals with lower attachment security. This hypothesis was also supported: Individuals high in attachment anxiety especially benefited from leader secure-base support in terms of its effect on role breadth self-efficacy; whereas those who are high in attachment avoidance especially benefited from leader secure-base support in terms of its effect on autonomous motivation. Our study helps explain how leaders’ support motivates employees’ proactive behavior, particularly for those individuals who have lower attachment security.